Effects of defects on mechanical properties in metal additive manufacturing: A review focusing on X-ray tomography insights. (February 2020) - du Plessis, Anton; Yadroitsava, Ina; Yadroitsev, Igor
Abstract: X-ray tomography has emerged as a uniquely powerful and non-destructive tool to analyze defects in additive manufacturing. Defects include unintended porosity, rough surfaces and deviations from design, which can have different root causes and can vary significantly among samples. Powder material properties, non-uniform delivery of the powder layer, deformation during manufacturing, deviations from optimal process-parameters caused by changes in the laser beam, the optical components and the scanning system operation, may result in lack of fusion pores, metallurgical pores, keyhole pores, etc. These different types of pores have different typical sizes, shapes and 3D distributions. All types of defects have effects on the mechanical properties of a final part. The use of X-ray tomography to visualize pores in parts (non-destructively) prior to mechanical testing has allowed us to improve our understanding of the effect of this porosity on the mechanical properties of the part (also referred to as "effect of defect"). This can provide the possibility to discriminate critical defects from harmless ones, and thereby build confidence in additive manufacturing processes. This paper reviews the current state of knowledge with regard to the "effect of defect" in metal additive manufacturing, and highlights some relevant examples from our recent work. Graphical abstract: Unlabelled Image Highlights: Effects of defects on mechanical properties in metal additive manufacturing are reviewed. The review focussed on insights from X-ray tomography. Not all pores are harmful - smallest pores are harmless. Porosity influences both ductility and strength. Near-surface pores critical for fatigue properties